Spectrophotometric determinationof trace nitrite with a novel self-coupling diazotizing reagent: J-acid - Wei Wu; Wenhuan Wenjian Shi; Yuanxing Huang; Haixin Gu; Jingzhi Wang; Wenxuan Feng (Химия и технология воды, 2015)
A simple and sensitive method for the spectrophotometric determination of nitrite was described and optimum reaction conditions along with other important analytical parameters were established. In the presence of potassium bromide at 25°C, nitrite reacted with J-acid in hydrochloric acid producing diazonium salt and then coupled with excess J-acid in the sodium carbonate solution yielding red colored azo compounds. At wavelength of 500 nm, Beer’s law was obeyed over the concentration range of 0,02 – 0,60 mg∙L⁻¹. The molar absorptivity was 3,92∙10⁴ L∙mol⁻¹∙cm⁻¹. This method was easily applied to the determination of trace nitrite in environmental water with recoveries of 9₈,7 – 101,2%.